2020
DOI: 10.1177/1091581820948454
|View full text |Cite
|
Sign up to set email alerts
|

Range of Neurological Signs in Cynomolgus Monkeys After Intrathecal Bolus Administration of Antisense Oligonucleotides

Abstract: Intrathecal (IT) dosing (ie, injection into the subarachnoidal space at the lumbar region) is a common route of administration in cynomolgus monkey preclinical safety studies conducted for antisense oligonucleotides (ASO) that target central nervous system diseases. Herein we report on neurological signs that have been observed in 28 IT studies conducted in 1,016 cynomolgus monkeys. Neurological signs were classified into 5 groups: (1) A nonadverse transient absence of lower spinal reflexes. This observation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 1 publication
1
19
0
Order By: Relevance
“…These changes correlated with transient neurological observations noted at 2 and/or 6 hrs post dose which included decreased proprioceptive hindlimb positioning, decreased or absent tactile and/or visual hindlimb placing reaction, decreased or absent hindlimb flexor reflex and/or decreased muscle tone (data not shown). These types of reactions are rather typical for intrathecally dosed ASOs and are generally not adverse ( 24 ). In terms of histopathological analysis, test item related findings of neuronal vacuolation in the nervous system, vacuolated macrophages in spinal cord, injection site and lymph nodes, and basophilic granules in the kidneys were not considered adverse based on their low severity and lack of associated degenerative/inflammatory changes or clinical pathological changes (assessing renal function).…”
Section: Resultsmentioning
confidence: 99%
“…These changes correlated with transient neurological observations noted at 2 and/or 6 hrs post dose which included decreased proprioceptive hindlimb positioning, decreased or absent tactile and/or visual hindlimb placing reaction, decreased or absent hindlimb flexor reflex and/or decreased muscle tone (data not shown). These types of reactions are rather typical for intrathecally dosed ASOs and are generally not adverse ( 24 ). In terms of histopathological analysis, test item related findings of neuronal vacuolation in the nervous system, vacuolated macrophages in spinal cord, injection site and lymph nodes, and basophilic granules in the kidneys were not considered adverse based on their low severity and lack of associated degenerative/inflammatory changes or clinical pathological changes (assessing renal function).…”
Section: Resultsmentioning
confidence: 99%
“…These transient changes in spinal reflexes were considered non-adverse and represented an oligonucleotide class-specific finding after i.th. administration [44]. A recently published paper by Korte et al described these effects as not necessarily ASO-related, since they also occurred in aCSF-treated animals, indicating the dosing procedure per se influences neurological parameters [45].…”
Section: Discussionmentioning
confidence: 95%
“…A recently published paper by Korte et al described these effects as not necessarily ASO-related, since they also occurred in aCSF-treated animals, indicating the dosing procedure per se influences neurological parameters [45]. Further, persistent loss of one or more reflexes was described as non-adverse, since no fundamental physiological deficit or behavioral alterations were noted [44]. Following 13 weeks of intrathecal NVP-13 treatment, mononuclear cell infiltrates in the nervous system were considered to have resulted from proinflammatory effects of ASOs.…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical toxicology findings were consistent with those observed with intrathecal administration of other oligonucleotides. 97 In non-Good Laboratory Practice studies in nonhuman primates, at levels above the NOAEL, hind limb paresis was observed. At extremely high dose levels, acute convulsions were observed.…”
Section: Toxicologymentioning
confidence: 99%